Active listening 3 - Brown, Steven (Cambridge University Press, 2007)
Active Listening, Second edition is grounded in the theory that learners are more successful listeners when they activate their prior knowledge of a topic. Through a careful balance of activities, students learn to listen for main ideas, to listen for details, to listen and make inferences - and finally to progress from listening to personalized speaking.